The Unfolded Protein Response: At the Intersection between Endoplasmic Reticulum Function and Mitochondrial Bioenergetics - Carreras-Sureda, Amado; Pihán, Philippe; Hetz, Claudio (Frontiers in Oncology, 2017)
Endoplasmic reticulum (ER) to mitochondria communication has emerged in recent years as a signaling hub regulating cellular physiology with a relevant contribution to diseases including cancer and neurodegeneration. This functional integration is exerted through discrete interorganelle structures known as mitochondrial associated membranes (MAMs). At these domains ER/mitochondria physically associate to dynamically adjust metabolic demands and the response to stress stimuli. Here we provide a focused overview of how the ER shapes the function of the mitochondria, giving a special emphasis to the significance of local signaling of the unfolded protein response (UPR) at MAMs. The implications to cell fate control and the progression of cancer are also discussed.